2023
DOI: 10.23736/s1973-9087.22.07457-3
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of telehealth core exercises during COVID-19 after bariatric surgery: a randomized controlled trial

Abstract: BACKGROUND Bariatric surgery (BS) is presently the most durable and effective intervention to address severe obesity. BS results in significant weight loss and body composition changes, with reductions in both fat mass and lean mass. Conequently, muscle tissue wasting and a reduction in muscle strength and endurance seem to take place. Some studies have evaluated the impact of resistance training on changes in lean body mass and muscle strength either alone or along with protein supplementation in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…Regarding randomization, 61% presented low risk of bias, 21,36–41,43,50–53,55,57,59,61,62 21% had some concerns, 44–46,48,58,60 and 18% presented high risk of bias 42,47,49,54,56 . For deviations from intended interventions, 36% had a low risk, 21,36,39,41–43,45,50–52 while 50% raised some concerns 38,40,44,46,48,49,53,56,57,59–62 . However, bias in measuring outcomes (79%) and selecting reported results (89%) was generally low in most studies (Figure S3).…”
Section: Resultsmentioning
confidence: 99%
“…Regarding randomization, 61% presented low risk of bias, 21,36–41,43,50–53,55,57,59,61,62 21% had some concerns, 44–46,48,58,60 and 18% presented high risk of bias 42,47,49,54,56 . For deviations from intended interventions, 36% had a low risk, 21,36,39,41–43,45,50–52 while 50% raised some concerns 38,40,44,46,48,49,53,56,57,59–62 . However, bias in measuring outcomes (79%) and selecting reported results (89%) was generally low in most studies (Figure S3).…”
Section: Resultsmentioning
confidence: 99%
“…Monitoring patients during follow-up, access to health care, and social support have to be provided more than before [ 45 ]. Also, telehealth, as a helpful method to improve patients' rehabilitation, should be considered more than before; telehealth core exercises and even telephone-based cognitive behavioral therapy may help patients have a better postoperative period [ 46 , 47 ]. So, further supports concerning food security, accessing health care, and new physical activity routines are mandatory to achieve better results [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…The most widely used indicators of muscle fatigue are the rate of the decrease in median frequency (MF) and the simultaneous rise in EMG amplitude (RMS) during submaximal sustained contraction [24]. Using McGill's torso muscular endurance tests, Ali et al [25] found that trunk muscle endurance decreased after BS in comparison to their controls.…”
Section: Introductionmentioning
confidence: 99%